Penerapan Model Kooperatif Tipe Student Teams Achievement Divisions (STAD) dalam Pembelajaran IPS Sejarah untuk Meningkatkan Hasil Belajar peserta didik - Tomagola, Leni M.S. (Peneliti.net, 2024)
This research aims to determine the application of the Student Team Achievement Division (STAD) type cooperative model in learning History Social Studies to improve learning outcomes for class VIII students at SMA Negeri 3 Gambesi. The method used in this research is descriptive qualitative from the results of classroom action research (PTK) through two cycles. The subjects of this research were 25 class VIII students. The research results show that the application of the Student Teams Achievement Divisions (STAD) type cooperative model in History Social Studies Learning to Improve Learning Outcomes for class VIII students can improve student learning outcomes. This is based on the post test scores, student learning outcomes have increased in each cycle, starting from the pre-cycle, the classical KKM achievement was 44% with an average score of 63.2; Cycle I achieved classical completeness with a percentage of 72% with an average score of 75.4; Cycle II achieved classical completeness with a percentage of 92% with an average score of 82.6.